Pendidikan Karakter Anak dalam Kitab Ayyuhal Walad Karya Imam Al-Ghazali - Nur Khosiin; Ulfa Lailatul Maulidiyah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2022)
Character education basically forms a noble nation. Good education and a religious environment will give birth to an education and religious generation. The book Ayyuhal walad is on of the works of imam al ghazali which contains about character education advice, this was addressed to one of his students who asked him for advice. Among the character education contained in the book are : religious values, tolerance, honesty, discipline, curiosity, responsibility and others. If this is applied to children, it is not only a moral message or mere advice but will form good character and a noble character, which will later become moral and civilized generations.